Soybean TIP Gene Family Analysis and Characterization of GmTIP1;5 and GmTIP2;5 Water Transport Activity - Song, Li; Nguyen, Na; Deshmukh, Rupesh K.; Patil, Gunvant B.; Prince, Silvas J.; Valliyodan, Babu; Mutava, Raymond; Pike, Sharon M.; Gassmann, Walter; Nguyen, Henry T. (Frontiers in Plant Science, 2016)
Soybean, one of the most important crops worldwide, is severely affected by abiotic stress. Drought and flooding are the major abiotic stresses impacting soybean yield. In this regard, understanding water uptake by plants, its utilization and transport has great importance. In plants, water transport is mainly governed by channel forming aquaporin proteins (AQPs). Tonoplast intrinsic proteins (TIPs) belong to the plant-specific AQP subfamily and are known to have a role in abiotic stress tolerance. In this study, 23 soybean TIP genes were identified based on the latest soybean genome annotation. TIPs were characterized based on conserved structural features and phylogenetic distribution. Expression analysis of soybean TIP genes in various tissues and under abiotic stress conditions demonstrated tissue/stress-response specific differential expression. The natural variations for TIP genes were analyzed using whole genome re-sequencing data available for a set of 106 diverse soybean genotypes including wild types, landraces and elite lines. Results revealed 81 SNPs and several large insertions/deletions in the coding region of TIPs. Among these, non-synonymous SNPs are most likely to have a greater impact on protein function and are candidates for molecular studies as well as for the development of functional markers to assist breeding. The solute transport function of two TIPs was further validated by expression in Xenopus laevis oocytes. GmTIP1;5 was shown to facilitate the rapid movement of water across the oocyte membrane, while GmTIP2;5 facilitated the movement of water and boric acid. The present study provides an initial insight into the possible roles of soybean TIP genes under abiotic stress conditions. Our results will facilitate elucidation of their precise functions during abiotic stress responses and plant development, and will provide potential breeding targets for modifying water movement in soybean.